A novel homozygous truncating mutation of the SFRP4 gene in Pyle's disease. Issue 1 (16th January 2017) - Chatron, N.; Lesca, G.; Labalme, A.; Rollat‐Farnier, P.A.; Monin, P.; Pichot, E.; Edery, P.; Sanlaville, D.; Rossi, M.
Abstract :